Comprehension strategies used by the Islamic senior high school students during shadow reading - Arlina; Iskandar (International Journal of Humanities and Innovation (IJHI), 2019)
This research aims at finding out comprehension strategies used by the students during shadow reading. This research is qualitative research with classroom observation. This research is based on Vygotsky's sociocultural theory that involves scaffolding and zone of proximal development (ZPD). The data is analyzed through problem-solving as comprehension analysis. The comprehension strategies are focused on three aspects of reading namely phonological processing, word recognition, and syntactical processing. This research is restricted to the interactional phase of shadow reading and focused during reading only. The result shows that from those three focuses, there are six comprehension strategies. In the phonological processing, there are repairing incorrect utterance of partner and dividing a word into manageable sound. In the word recognition, there are implicitly asking for repetition to complete the task and giving repetition for incorrect word. In the syntactical processing, there are modifying input in manageable repetition and explicitly requesting repetition to complete the task. Those strategies help the shadower to complete the task. Thus, they can reach ZPD.